1981
DOI: 10.1007/bf00210516
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of Kupffer cells in teleost liver under normal and experimental conditions

Abstract: The Kupffer cells in the liver of the teleost fish, Pimelodus maculatus, are attached by desmosomes to the endothelial cells lining the sinusoids. These provide a strong attachment allowing them to resist the passage of blood. Following perfusion with India ink, both endothelial and Kupffer cells ingest India ink particles by pinocytosis and micropinocytosis. It is suggested that both cell types may represent two different functional states of the same cell.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Apparently absent in certain salmonids (McCuskey et al, 1986), resident sinusoidal macrophages appear to be present in ictalurid (Hinton and Pool, 1976; the present study), and perhaps other teleost species (Fujita et al, 1980;Ferri and Sesso, 1981;Hinton et al, 1984). It appears from the results of the present study that resident sinusoidal macrophages of the bullhead catfish liver share many of the ultrastructural and function characteristics of mammalian Kupffer cells.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Apparently absent in certain salmonids (McCuskey et al, 1986), resident sinusoidal macrophages appear to be present in ictalurid (Hinton and Pool, 1976; the present study), and perhaps other teleost species (Fujita et al, 1980;Ferri and Sesso, 1981;Hinton et al, 1984). It appears from the results of the present study that resident sinusoidal macrophages of the bullhead catfish liver share many of the ultrastructural and function characteristics of mammalian Kupffer cells.…”
Section: Discussionmentioning
confidence: 56%
“…In the present study, sinusoidal macrophages were only observed to be anchored to endothelial cells by numerous desmosomes or desmosome-like densities. Similar junctions between macrophages and sinusoidal endothelial cells have been reported in Zctalurus punctatus (Hinton and Pool, 1976) and Pimelodus maculatus (Ferri and Sesso, 1981). In other teleost species, junctions between macrophages and supporting cells seen in the atrium of the heart, spleen, and kidney have not been described.…”
Section: Discussionmentioning
confidence: 66%
“…The endothelial cells in the liver of the teleost fish Pimelodus maculatus Lacepède are able to take up India ink particles (Ferri & Sesso, 1981). The present result revealed that the liver endothelial cells in platies cannot accumulate foreign ferritin.…”
mentioning
confidence: 46%
“…The Kupffer and the sinusoidal endothelial cells are linked by the spot desmosomes to provide a strong attachment and prevent the Kupffer cells from being washed away by the blood. Ferri and Sesso (1981) also reported Kupffer cells in the liver of Pimelodus maculatus, but Tanuma et al (1982) and Rocha et al (1994) stated that no classical Kupffer cells are present in the liver of Kareius bicoloratus and Salmo trutta fario, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…They also added that the livers of Pagothenia borchgrevinki, Trematomus bernacchii and Gymnodraco acuticeps, have a few number of the perisinusoidal cells that contain very few lipid droplets. Ferri and Sesso (1981) reported that the liver of Pimelodus maculates has polymorphic Kupffer cells, which contain vacuoles varying widely in diameter, density and shape. They also suggested that these Kupffer cells and the endothelial cells may represent two different functional states of the same cell type.…”
Section: Introductionmentioning
confidence: 99%